Multiple case study analysis - Stake, Robert E. 1927- (The Guilford Press, 2006)
Three actual case reports from a transnational early childhood program illustrate the author's approach, and helpful reproducible worksheets facilitate multicase recording and analysis. Book jacket."--BOOK JACKET
Literaturverzeichnis Seite 327-332
Keywords: Step by Step (Programme); Step by Step (Programme) - Études transculturelles; Step by Step (Program) -- Cross-cultural studies; Cas, Méthode des; Casestudies; Éducation - Europe de l'Est - Études transculturelles; Éducation - Recherche - Méthodologie; Erziehung; Case method; Education -- Research -- Methodology; Education -- Europe, Eastern -- Cross-cultural studies; Forschung; Pädagogik; Empirische Sozialforschung; Fallstudie; Osteuropa